Comparison of human detection using background subtraction and frame difference - Mohd Saifulnizam Zaharin; Norazlin Ibrahim; Tengku Mohd Azahar Tuan Dir (Bulletin of Electrical Engineering and Informatics, 2020)
Image processing is mostly used for exploring image behaviour. There are several steps in image processing. Image acquisition, pre-processing, feature extraction, and classification are the processes used for the detection of human movement based on high-level feature extraction (HLFE), in which HLFE was used for feature extraction in this paper. This study proposed the use of background subtraction and frame difference. This research was conducted to analyse the difference of background subtraction and frame difference methods based on movement of human. Movement of human detected by using feature extraction were centroid image technique used. Furthermore, support vector machine (SVM) was used for classification.